Antiplatelet therapy in acute coronary syndromes: focus on ticagrelor - Birkeland, Kade (Dove Medical Press, 2010)
The use of antiplatelet agents, specifically the thienopyridines, has become a standard of care in the approach to the patient presenting with an acute coronary syndrome. These drugs irreversibly inhibit the platelet by permanently binding to the surface P2Y12 receptor and blocking the downstream fibrinogen cross-linking between platelets, which leads to aggregation and thrombus. However, currently available therapeutic choices are limited by potential interaction with other medications, slow hepatic conversion to active metabolite, genetic resistance, and narrow therapeutic safety margin. In order to overcome these disadvantages, there has been an interest in developing alternatives to thienopyridines. Recent investigations have included ticagrelor, a reversible inhibitor of the P2Y12 platelet receptor, which appears to have overcome several drawbacks of the current thienopyridines. Its unique pharmacokinetic and pharmacodynamic profiles result in an inhibition of platelet aggregation that is rapid, high, consistent, and less susceptible to interpatient variability than currently available P2Y12 inhibitors. In addition, ticagrelor offers a potential mortality advantage not apparent with current agents. Although questions regarding the nature, magnitude, and clinical significance of several observed adverse effects (dyspnea and ventricular pauses) remain unanswered, it appears that ticagrelor may represent a significant advancement over currently available oral antiplatelet agents.